KULTUR MENULIS: SISI TILIK KEILMIAHAN PERGURUAN TINGGI - Maksimilianus Jemali (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
Writing is a scientific identity of the intellectuals. In academic sphere, the intellectuals do not only internalize ideas but also they should externalize ideas in writing. By writing, an intellectual person can manifest his/her ideas. Hence, writing is an inherent culture or habit. The inherence of writing habit makes university responsible for events around the world. As such, a good academic writing covers standard criterion that a writer needs to maintain and fulfill.